Theoretical and experimental investigation on the sudden unbalance and rub-impact in rotor system caused by blade off. (August 2016) - Wang, Cun; Zhang, Dayi; Ma, Yanhong; Liang, Zhichao; Hong, Jie
Abstract: Blade loss from a running turbofan rotor will introduce sudden unbalance into the dynamical system, and as a consequence leads to the rub-impact, the asymmetry of rotor and a series of interesting dynamic characteristics. The paper focuses on the theoretical study on the sudden unbalance and rub-impact caused by blade loss, in particular investigates the response of the rotor on a rotor test rig with sudden unbalance and rub-impact device designed respectively. The results reveal that the sudden unbalance will induce impact effect on the rotor, and critical speed frequency is excited in frequency spectrum. Meantime, the impact effect is more obvious for the rotor operating above critical speed. The influence of rub-impact is considered as additional constraint to the rotor, analyzed by the theory of time-varying system for the first time, and the results are evaluated by experimental tests. The study shows that great attention should be paid to the dynamical design for the overhung rotor system, additional constraint and corresponding analysis method in rub-impact need to be intensively studied. Highlights: The sudden unbalance and rub-impact induced by blade loss is investigated by mechanism analysis and simulated tests. The influence of rotating speed, geometry layouts and damping on the impact effect are obtained. The time-varying parameters method is induced to study the additional constraint for the first time with good effect. The rotor operates above critical speed is more sensitive to sudden unbalance. Test rig equivalent to low pressure rotor of high bypass ratio turbofan engine in structure and dynamic is built.